The Impact of Digital Climate on Employee Wellbeing in the Digital Transformation Era - Ziv Avtalion; Itzhak Aviv; Irit Hadar; Gil Luria; Oshri Bar-Gil (IEEE Access)
Organizations pursuing enduring success in the digital transformation era need to understand employee interactions with rapidly changing technologies. Our research introduces digital climate as a vital organizational climate subdimension that represents employee views about technology readiness, digital resources, and digital leadership. A Grounded Theory research method was used in a public government organization to conduct 25 semi-structured interviews, which uncovered three main digital climate dimensions, including User Digital Experience, Digital Process Efficiency, and Organization’s Digital Effectiveness. Employee involvement in digital tool selection and customization combined with workflow optimization and rapid technical support delivery leads to improved employee well-being through technostress reduction, burnout prevention, and job satisfaction enhancement. The research demonstrates how digital climate affects employee well-being, providing scholars and practitioners with tools to measure and control digital transformation’s impact on employee well-being for sustainable competitive advantage in contemporary workplaces and future development.